2022
DOI: 10.3390/rs14030578
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ionospheric Scintillation Radio Propagation Characteristics with Cosmic Observations

Abstract: The ionosphere has important influences on trans-ionosphere radio propagation. When signals pass through ionospheric irregularities, their amplitude and phase are often attenuated and distorted. In this work, the statistical features of scintillation observed by the Global Navigation Satellite System (GNSS) and low earth orbit (LEO) satellites are investigated with Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) data in solar cycle 24. The amplitude scintillation propagation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Despite these results, the signature is still weak and should not be considered an early earthquake warning system. Therefore, it is essential to study if additional geophysical variables, such as LST anomalies [16], magnetic field anomalies from Swarm [59], [60], or IS derived from GNSS-RO measurements [61]…”
Section: Discussionmentioning
confidence: 99%
“…Despite these results, the signature is still weak and should not be considered an early earthquake warning system. Therefore, it is essential to study if additional geophysical variables, such as LST anomalies [16], magnetic field anomalies from Swarm [59], [60], or IS derived from GNSS-RO measurements [61]…”
Section: Discussionmentioning
confidence: 99%
“…A validation in terms of electron density data observed by MetOp-A is provided by [36]. In the present work, we carry out the validation directly over the bending angle [37,38] and signal fading observations [39][40][41], providing additional validation over the MetOp-A dataset. Details of the dataset collected by the MetOp-A satellite and other RO missions used for comparisons are presented in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies at frequencies appropriate to V/UHF communication systems by Whitney et al (1972) and Whitney and Basu (1977) explored the characteristics of amplitude scintillation on 137 and 360 MHz communications channels, finding that the channel can be described by a Nakagami-m distribution such that when the scintillation is intense, m = 1 and the distribution is Rayleigh. More recently, Chen et al (2022) have suggested the use of other models. A widely used index to describe amplitude scintillation is S 4 , being the root-mean-square of the power P divided by the average power, 𝐴𝐴 𝑃𝑃 (Briggs & Parkin, 1963) and this will be used extensively in this paper:…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Chen et al. (2022) have suggested the use of other models. A widely used index to describe amplitude scintillation is S 4 , being the root‐mean‐square of the power P divided by the average power, trueP $\overline{P}$ (Briggs & Parkin, 1963) and this will be used extensively in this paper: S4=0.25em][true140%PP20.5P ${S}_{4}=\,\frac{{\left[\sum {\left(P-\overline{P}\right)}^{2}\right]}^{0.5}}{\overline{P}}$ …”
Section: Introductionmentioning
confidence: 99%